Uma análise da evolução da área plantada da cana de açúcar no estado de São Paulo nos últimos 10 anos - Chaguri, Ana Beatriz [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This paper analyzes the evolution of the sugar cane plantation area in the State of São Paulo in the last ten years. It presents a concise report about the history of this raw material in the country and describes how the sector relating to sugar cane was before the economic deregulation and what changes occurred after 1990, emphasizing the territorially expansion occurred in the State of São Paulo. The paper concludes that the expansion of the sector relating to sugar cane occurred much more territorially than through productivity gains, considering that these ganis were bigger in the State of São Paulo, and that the economic deregulation left a legate of heterogeneity in this sector

Este texto analisa a evolução da área plantada de cana de açúcar no Estado de São Paulo, nos últimos dez anos. Apresenta um breve relato sobre a história desta matéria prima no país, descrevendo como o setor canavieiro era antes da desregulamentação econômica e quais as mudanças ocorridas após 1990, com ênfase na expansão territorial ocorrida no estado de São Paulo. O trabalho conclui que a expansão canavieira ocorreu muito mais territorialmente do que por meio de ganhos de produtividade, tendo em vista que esses ganhos foram maiores no estado paulista e que a desregulamentação econômica deixou um legado de heterogeneidade neste setor
Keywords: Economia; Cana-de-açúcar; Expansão territorial canavieira; Desregulamentação econômica; Sugar cane; Economic deregulation; Territorially expansion